Stiffness-based Spring Design Optimization using Taguchi Method to reduce Low-Frequency Vibration - Ahmad Yusuf Ismail; Al Munawir; Noerpamoengkas A (universitas teuku umar, 2019)
Low-frequency vibration has been troublesome for a mechanical system. Despite the measurement difficulties, low-frequency vibration also creates several environmental effects such as high noise level that is harmful to the human body. One of the methods to reduce vibration is tuning the vibration isolation i.e. spring and damping coefficient. However, the latter method is found to be effective only for the mid-high frequency range. Therefore, this paper proposes an optimization of the spring a.k.a. stiffness coefficient in order to reduce the low-frequency vibration. The Taguchi method is used as an optimization tool since it offers simplicity yet powerful for any field of application, particularly in engineering. Two significant parameters in the spring geometry were selected as the optimization variable in the Taguchi method and evaluated using vibration transmissibility concept. The result shows that the Taguchi method has been successfully obtained the optimum value for the spring geometry purposely to reduce the vibration transmissibility.